2021
DOI: 10.2196/preprints.33450
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Problematic Social Media Use in Adolescents and Young Adults: Systematic Review and Meta-analysis (Preprint)

Abstract: UNSTRUCTURED This study sought to systematically examine problematic social media use in youth and its association with symptoms of depression, anxiety, and stress. Our hypothesis was that problematic social media use increased the risk of each mental health outcome measure. A systematic search was conducted to identify studies in adolescents and young adults, using the databases Engineering Village, Psychinfo, Pubmed, and Web of Science. A total of 21 studies were identified in our re… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 55 publications
0
0
0
Order By: Relevance
“…It is important to note that some studies have shown complex nuances, small effects, or mixed results in relation to social media use and wellbeing (Orben and Przybylski, 2019;Kross et al, 2020;McFarland et al, 2023). However, many investigations and reports have come to light which demonstrate how negative engagement with technology can lead to adverse consequences such as increased suicidal ideation, depression, anxiety, problematic social media use, violence, hate speech, and other consequences, including negative mental health effects in groups such as teenagers (Kavanagh et al, 2019;60 Minutes, 2021;Castaño-Pulgarín et al, 2021;Huang, 2022;Shannon et al, 2022).…”
Section: Engaging With Technologymentioning
confidence: 99%
“…It is important to note that some studies have shown complex nuances, small effects, or mixed results in relation to social media use and wellbeing (Orben and Przybylski, 2019;Kross et al, 2020;McFarland et al, 2023). However, many investigations and reports have come to light which demonstrate how negative engagement with technology can lead to adverse consequences such as increased suicidal ideation, depression, anxiety, problematic social media use, violence, hate speech, and other consequences, including negative mental health effects in groups such as teenagers (Kavanagh et al, 2019;60 Minutes, 2021;Castaño-Pulgarín et al, 2021;Huang, 2022;Shannon et al, 2022).…”
Section: Engaging With Technologymentioning
confidence: 99%
“…Social media har blivit en central del av ungdomars liv och över 80 procent av ungdomar mellan 15-17 år använder sociala medier dagligen (Kreski et al, 2021). Men det har också väckt frågan om hur det påverkar ungdomars välbefinnande och sömn negativt (Shannon et al, 2022). Forskning har kopplat användning av social media med minskad sömnlängd och ökad dagtrötthet (Levenson et al, 2017;Lissak, 2018).…”
Section: Introduktionunclassified
“…[8] Previous studies exploring the detrimental consequences linked to the utilization of social media have revealed that the presence of problematic social media usage can result in a decline in an individual's psychological welfare and overall physical condition. [9,10] The impact of social media on mental health has emerged as a prominent facet of societal dynamics. There has been an increasing apprehension regarding the influence of prolonged engagement with these platforms on the psychological well-being of individuals.…”
Section: Introductionmentioning
confidence: 99%